. Description of Learning Motivation among Female Adolescent Survivors of Sexual Violence in Makassar - Djoeddawi, Siti Naga Uleng Purnama Sari; Dewi, Eva Meizara Puspita (Polteknik Ilmu Pemasyarakatan, 2023)
. Motivation to learn is one aspect of supporting young women in pursuing education. However, there are teenage girls whose motivation to learn is influenced by the sexual violence they experience. The aim of the research is to determine the description of sexual violence, learning motivation and learning motivation factors among survivors of sexual violence in Makassar. This research is a qualitative phenomenological research. The research subjects were 3 female teenagers aged 20 – 22 years who were students in Makassar. Data was collected through an interview process which resulted in interview transcripts and voice recording documentation. The data that has been coded is then analyzed for the suitability of interpretation between the subject and the researcher. This research found that adolescent girls experience sexual violence in the family, school, campus and public places which has an impact on their physical, psychological, spiritual, learning processes and outcomes. However, teenagers continue to learn and overcome learning obstacles in order to fulfill their dreams and hopes. Factors that shape teenagers' learning motivation include internal factors and external factors. Internal factors are needs and aspirations, while external factors are social support from family and peers. It is hoped that this research will provide an understanding regarding learning motivation and the factors that shape learning motivation in female adolescent survivors of sexual violence. The conclusion of this research is that even though sexual violence has an impact on the physical and psychological impact of adolescent girls, adolescents still have good motivation to study because of the internal and external factors that support adolescents.